Clinical safety of dichlorvos (45%), cypermethrin (5%) and piperonyl butoxide (25%) administered by spray on the skin of cattle - Moraes, Alessandra C. [UNESP]; Prado, J. R. [UNESP]; Faria, Vanessa P. [UNESP]; Girio, Thais M. S.; Manrique, Wilson G. [UNESP]; Belo, Marco A. A. [UNESP] (Univ Cordoba, 2015)
Objective. Due to the importance of controlling ectoparasites, associated with the necessity of technical knowledge on the safety of topical treatment with organophosphates, pyrethroids and piperonyl butoxide to the animal organism, this bioassay was carried out to evaluate the clinical safety of the association of dichlorvos (45%) + cypermethrin (5%) + piperonyl butoxide (25%) administered by spray on the skin of cattle, through the study of clinical parameters, biochemical, haematological and behavioral changes. Materials and methods. Sixteen crossbred animals with a mean age of 18 months, males and females grouped into two treatments with eight animals each: T1 (1: 800 v/v) and T2 (1: 200 v/v). Were collected blood samples at six different times: before treatment (BT), 24, 48, 72, 96 and 192 hours post treatment (HPT). Results. The antiparasitic association administered by spray on the skin did not result in changes in the enzymatic activity of ALT, AST, GGT and ALP, as well as in serum albumin, triglycerides, cholesterol, urea and creatinine, demonstrating the safety of this antiparasitic compound for maintaining hepatic and renal functionality. The erythrocyte, leukocyte and platelet studies showed no changes caused by treatments, and no clinical signs and behavioral changes were observed after treatment. Conclusions. These findings demonstrated good safety margin for spray treatment on the skin with this antiparasitic compound, even when administered at a dilution of 1: 200 v/v, which is four times the dose recommended for ectoparasite control.
Keywords: Clinical safety; bovine; organophosphates; piperonyl butoxide; pyrethroids; spray (Source: DeCS, USDA)